Favorable rates of cardiovascular events with stringent cardiovascular monitoring and a lowered dose of ponatinib as second-line treatment in chronic phase chronic myeloid leukemia patients failing or intolerant to first-line second-generation tyrosine kinase inhibitor treatment: results of the prospective PONS trial - Le Coutre, Philipp; Burchert, Andreas; Saußele, Susanne; Schwarzer, Thekla; Stintzing, Sebastian; Pelzer, Uwe; Bullinger, Lars; Elmaaḡaçlı, Ahmet Hayri; Jehn, Christian-Friedrich; Stegelmann, Frank; Hochhaus, Andreas; Ernst, Thomas; et al. (Acta haematologica, 2025)
Introduction: In chronic myeloid leukemia patients, second-line treatment requires careful consideration of response and tolerability. As most patients need a more efficient tyrosine kinase inhibitor, ponatinib at a lowered dose should be evaluated in this setting. Methods: We studied a lowered dose of 30 mg ponatinib in second line in patients selected toward a low cardiovascular risk. In 22 screened patients, ponatinib was started in 18 patients previously treated with imatinib (n = 3), dasatinib (n = 9), or nilotinib (n = 6). Patients were frequently monitored for cardiovascular toxicities by testing of blood pressure, vital signs, ankle brachial index or duplex, oral glucose tolerance test, echocardiography, ECG, and fundoscopy. The study protocol allowed dose reductions in patients achieving MMR. Both previously resistant or intolerant patients were recruited. Results: No serious cardiovascular events were observed, and low-grade cardiovascular toxicity was negligible. By 12 months, 13 patients (92.9%) were in complete hematologic remission, 10 patients (55.6%) were in MMR, and 5 patients (27.8%) were in MR4. Most importantly, we demonstrated that thorough monitoring of cardiovascular risk is feasible. Conclusions: We demonstrated that a lowered dose of 30 mg ponatinib in selected patients can be maintained without serious cardiovascular complications, provided cardiovascular risk monitoring is performed. In our patient cohort, this approach resulted in favorable response rates.